Penyuluhan Perlindungan Hak Reproduksi Perempuan Bagi Ibu Ibu Kelompok Tani Desa Cipadang Gedong Tataan - Putri, Yunita Maya; Putri, Ria Wierma; Kasmawati, Kasmawati; Oktaviana, Selvia; Susanti, Emilia (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2024)
Reproductive rights are the basic rights of every individual or couple to be able to freely and responsibly decide the number, spacing of births, and time to have children, so as to obtain good quality in reproductive health. Protection of reproductive rights for women is important to prepare new humans as superior future generations. Protection of women's reproduction is needed to guarantee legal protection in their growth and development and human rights that are recognized while in the womb. This service aims to provide counseling and interactive discussions to mothers of the Cipadang Gedong Tataan Village farmer group regarding the protection of women's reproductive rights so that these rights are not misused. Increase knowledge, understanding and legal awareness of the community, especially to mothers of the Cipadang Gedong Tataan Village farmer group regarding the protection of women's reproductive rights. This service provides important insights for mothers of the Cipadang Gedong Tataan Village farmer group regarding the protection of women's reproductive rights. The implication of this service is that universities and non-governmental organizations must encourage and support this service activity so that the community understands the protection of women's reproductive rights.